2010
DOI: 10.1002/ptr.3237
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐allergic effects of total bakkenolides from Petasites tricholobus in ovalbumin‐sensitized rats

Abstract: The anti-allergic effect of total bakkenolides from the rhizome of Petasites tricholobus (BAPT) was evaluated in an ovalbumin-induced allergic rhinitis model in male Wistar rats. The major components of the bakkenolide fraction are bakkenolide-D, bakkenolide-B, bakkenolide-IIIa and bakkenolide-IVa, which account for 60.04% of the total. The rats were treated with 40 mg/kg, 20 mg/kg, 10 mg/kg or 5 mg/kg BAPT, and 0.942 mg/kg loratadine and 0.5% gum tragacanth were used as positive and negative controls, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…P. japonicus has been used to treat various diseases, including headaches, chronic cough, fever, and asthma. A bioassay study has demonstrated that P. japonicus extracts and compounds have antioxidant, anti-inflammatory, and antitumor biological effects (22). P. japonicus bakkenolide B has been previously demonstrated by our group to exhibit both antiallergenic and anti-inflammatory effects (23).…”
Section: Petasites Japonicus Bakkenolide B Inhibits Lipopolysaccharidmentioning
confidence: 93%
“…P. japonicus has been used to treat various diseases, including headaches, chronic cough, fever, and asthma. A bioassay study has demonstrated that P. japonicus extracts and compounds have antioxidant, anti-inflammatory, and antitumor biological effects (22). P. japonicus bakkenolide B has been previously demonstrated by our group to exhibit both antiallergenic and anti-inflammatory effects (23).…”
Section: Petasites Japonicus Bakkenolide B Inhibits Lipopolysaccharidmentioning
confidence: 93%
“…Moreover, some active extracts rich in bakkenolides also showed interesting pharmacological activities. A bakkenolide fraction with bakkenolide D, B, IIIa and Iva as the major components has shown beneficial effects on allergic rhinitis in ovalbumin‐sensitized Wistar rats (Zhang et al ., ). The methanol extracts of P .…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, some active extracts rich in bakkenolides also showed interesting pharmacological activities. A bakkenolide fraction with bakkenolide D, B, IIIa and Iva as the major components has shown beneficial effects on allergic rhinitis in ovalbuminsensitized Wistar rats (Zhang et al, 2011). The methanol extracts of P. japonicus have been reported to protect from brain damage (Sok et al, 2006), suppress preadipocyte differentiation, reduce visceral fat accumulation (Watanabe et al, 2010) and inhibit ovalbumin-induced airway inflammation in rats (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from Petasites genus have been shown to have anti-allergic and anti-inflammatory effects ( Fiebich et al ., 2005 ; Lee et al ., 2011 ; Zhang et al ., 2011 ). Furthermore, lipophilic extracts of rhizomes of Petasites hybridus L., Asteraceae (the butterbur) have been used to treat asthma ( Danesch, 2004 ; Brattstrom et al ., 2010 ).…”
Section: Introductionmentioning
confidence: 99%